Ethanol and volatiles from castor bean cake on plant-parasitic nematodes control - Pedroso, Luma Alaís (2020)
The most plant-parasitc nematodes target the root system of plants preferentially and prevent translocation and absorption of nutrients, causing concern to producers. Therefore, the search for new control strategies is always important, because current strategies do not satisfy agribusiness. Some volatile organic compounds (VOCs) emitted by plants are toxic to plantparasitic nematodes and may result in the development of new nematicides. In this work, we evaluated the compounds γ-decalactone, skatole, phenol and 4-methylphenol emitted by castor bean cake when incorporated into the soil against Meloidogyne incognita, as well as the ethanol compound on Heterodera glycines control. With the exception of phenol, all the compounds emitted by castor bean cake reduced hatching of M. incognita second-stage juveniles (J2). Infectivity and reproduction decreased when J2 were in contact with the LC50 of the compounds followed by inoculation into soil with tomato plants, as well as when the compounds were applied at 500mg L -1 at the time of inoculation with J2. Phenol and 4-methylphenol caused a high percentage of J2 mortality and the fumigation of substrate containing M. incognita eggs with the compounds at 1000mg (L substrate) -1 , reduced the number of galls and eggs. When evaluating ethanol use against H. glycines J2 in solution and as well as a fumigant, the compound at low concentration was more effective by direct dipping than by fumigation, and J2 hatching was highly reduced by direct dipping. Fumigation of H. glycines infested soil with ethanol reduced nematode infectivity and reproduction. Ethanol at 48% concentration significantly reduced the J2 lipid content, in addition to internally altering the nematode body. Infectivity and reproduction of J2 were also reduced when the nematodes were in direct dipping with 6% ethanol. Therefore, the compounds γ-decalactone, skatole, phenol and 4-methylphenol act as nematicides in the M. incognita life cycle. Moreover, ethanol is toxic to H. glycines at low concentrations and affects its pathogenic behavior rather than simply reducing the lipids.